Variables affecting gestation period in gir dairy cattle - Aroeira, José Antonio D. C.; Sampaio, Ivan B. M. (Pesquisa Agropecuaria Brasileira, 2014)
Nine hundred and thirty four (934) gestation periods from a Gir herd under selection as dairy cattle, were studied to detect probable influences on parity years (1954/1972), calf weight and sex, season and sex, season and parity. Average gestation period was 286 days with a standard deviation of 11.4. The selected mathematical model was: estimated periods = 292.98 - 0.29 (parity)2 + 2.34 (parity) + 0.49 (weight of calf) 0.31 (year of parturition) where all variables were significant (P<0.05). Maximun gestation length was reached at parity four (288 days), as curvilinear effect was observed. Sex effect was probably absorbed in variable weight and all contrasts involving seasonal effect were not significant.